Boron-doped Fe-N-C single-atom nanozymes specifically boost peroxidase-like activity - Jiao, Lei; Xu, Weiqing; Zhang, Yu; Wu, Yu; Gu, Wenling; Ge, Xiaoxiao; Chen, Bingbing; Zhu, Chengzhou; Guo, Shaojun (Nano today, 2020)
Boron-doped Fe-N-C single-atom nanozymes with an intrinsic charge transfer achieve the significantly enhanced peroxidase-like activities and selectivities, which opens a new route in the rational design of more advanced nanozymes at the atomic scale and bridge the gap between nanozymes and natural enzymes. [Display omitted] •Boron-doped Fe-N-C single-atom nanozymes can be capable of selectively enhancing peroxidase-like activities.•Boron-induced charge transfer modulates the charge of Fe atom to accelerate the formation of hydroxyl radical.•Sensitive detection of acetylcholinesterase activity and corresponding pesticide was achieved. Nanomaterials with enzyme-like activities, i.e., nanozymes, have aroused wide concern in biocatalysis. Fe-N-C single-atom catalysts with atomically dispersed FeNx as active sites, defined as Fe-N-C single-atom nanozymes, have the structure similar to some heme enzymes and therefore can mimic the enzyme-like activities. However, they are still subject to the limited biocatalytic activity and selectivity because of the grand challenge in rationally tuning the electronic structure of central Fe atoms and achieving their superior performances approaching nature heme enzymes. Herein, we demonstrate that boron-doped Fe-N-C single-atom nanozymes with an intrinsic charge transfer can work much better and achieve the significantly enhanced peroxidase-like activities and selectivities. Theoretical calculations reveal that boron-induced charge transfer effects can be capable of modulating the positive charge of the central Fe atom to reduce the energy barrier of the formation of hydroxyl radical and therefore boost the peroxidase-like activity. The boron-doped Fe-N-C single-atom nanozymes can achieve vivid mimicking nature peroxidase and finally show their promising applications in the detection of enzyme activity and small molecule. This work opens a new route in the rational synthesis of more advanced nanozymes at the atomic scale and bridges the gap between nanozymes and natural enzymes.